2021
DOI: 10.4018/ijcewm.20210101.oa1
|View full text |Cite
|
Sign up to set email alerts
|

Cradle-to-Cradle in Project Management

Abstract: One of the most-recognized circular economy frameworks is the Cradle-to-Cradle design philosophy. However, integrating circularity in business practices impacts all organizational activities and not just the design of products and services. One of the business processes that needs to integrate sustainability is project management. The study reported in this article explores the integration of the Cradle-to-Cradle philosophy into project management practices. Based on a single in-depth case study, the integrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…First, the findings of this paper are in alignment with the RBV that suggests the significance of incorporating SPM practices to achieve PS. Nonetheless, this stream of research has lacked empirical evidence (Brones et al, 2014;Chawla et al, 2018;Moehler et al, 2018), hence there is a need to incorporate sustainability into the entire project life cycle in a holistic way (Ismayilova & Silvius, 2021;Martens & de Carvalho, 2014;Stanitsas et al, 2020). We showed that apart from triple-constraint criteria, integration of sustainability has become an important factor in the management of projects.…”
Section: Research Implicationsmentioning
confidence: 88%
See 1 more Smart Citation
“…First, the findings of this paper are in alignment with the RBV that suggests the significance of incorporating SPM practices to achieve PS. Nonetheless, this stream of research has lacked empirical evidence (Brones et al, 2014;Chawla et al, 2018;Moehler et al, 2018), hence there is a need to incorporate sustainability into the entire project life cycle in a holistic way (Ismayilova & Silvius, 2021;Martens & de Carvalho, 2014;Stanitsas et al, 2020). We showed that apart from triple-constraint criteria, integration of sustainability has become an important factor in the management of projects.…”
Section: Research Implicationsmentioning
confidence: 88%
“…For instance, Larson et al (2018) posited that the threat of global warming and climate change has brought sustainability to the fore. Accordingly, it is argued that SPM has become an increasing focus for project management (Hasheminasab et al, 2020;Pinto, 2020) and emerging literature suggests that PS is largely determined by how well firms manage and integrate critical sustainability issues at various stages of the project life cycle (Carvalho & Rabechini, 2017;Hasheminasab et al, 2020;Ismayilova & Silvius, 2021;Larsson & Larsson, 2020;Olawumi & Chan, 2019;Silvius & Schipper, 2015;Wo zniak, 2021;Yazici, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, cradle to cradle (C2C) is a paradigm oriented towards ecoeffectiveness [18] and a circular economy [53]. C2C defines a set of design principles as a guide for innovation and continuous improvement, considering environmental and social aspects, from the point of view of zero and positive impact (damage regeneration).…”
Section: Lca and C2c For Product Designmentioning
confidence: 99%
“…Source: Ismayilova and Silvius (2021) Within the context of eThekwini Municipality, the system boundary for a sustainable supply chain can now be stated as having eight phases. To develop a sustainable supply chain, eThekwini Municipality's supply chain management unit/department will need to examine each of these phases in terms of the impact on the triple bottom line.…”
Section: Final Dispositionmentioning
confidence: 99%